Implementasi Fuzzy Query dalam Sistem Pendukung Keputusan untuk Investasi Properti - Edelani, Renovita; Kusumaningtyas, Entin Martiana; Prasetyaningrum, Ira; Anggriawan, Bagus (Teknik Elektro Politeknik Negeri Padang, 2024)
Rapid urbanization and the increasing demand for residential property have created significant challenges in the real estate market. Prospective homebuyers often face difficulties in finding properties that meet their specific criteria in a crowded and competitive market. This research proposes an approach to property investment decision-making based on the Fuzzy Query method, providing a web-based application designed to simplify the property search process. The application allows users to filter properties based on various criteria, such as price, land area, building area, number of bathrooms, number of bedrooms, certificate type, and environmental noise levels. The application features an intuitive user interface that enables users to quickly find properties that match their preferences. This decision support system effectively assists property investors in obtaining investment assessments.